THE THEOLOGY OF RELIGIONS AND SACRIFICE - Thachil, Jose (Journal of Dharma, 1989)
In the past the attitude of the Christian Churches to non-christian religions, for dogmatic, psychological, social and cultural reasons had been dominated by condemnations and disqualifications. Both the content and tone of the declaration Nostra Aetate of Vatican Council I l bear witness to a decisive and unique advance from the earlier position. The spirit of this document justifies the expectation that both in theory and practice, the Church is willing and able to make its contribution to a world united in fraternity and peace.